Analyzing the Use of Dictions in the Opinion Column of Haluan Newspaper - Rizki, Restu; Septa, Rivaldo Trio; Rasyid, Yulianti (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
This study analyzed the use of diction in the opinion column in the November 1 to 5 2022 editions of the Haluan newspaper. The purpose of this research was to find and revise diction errors in the opinion column published in the newspaper. The method used in this research was descriptive qualitative method. The technique used in data collection was the technique of observing and noting. The results of this study indicated that there were many diction errors in the opinion column of the November 1 to 5 2022 editions of Haluan newspaper. From the results of this study, it can be concluded that the writers of Haluan newspaper must be more careful when publishing their opinions. Writers must observe and correct the writing of opinions before being published. Errors in diction in opinions can have fatal consequences because of the different perceptions and meanings of each person, which results in misunderstandings that can offend some readers, causing conflict and division within society.